2017
DOI: 10.12669/pjms.335.13685
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Balloon Dilatation for Achalasia Cardia; Early & late results, a single center study

Abstract: Objective:Achalasia Cardia is treated by Pneumatic balloon dilatation, Heller’s Myotomy and recently, by Peroral Esophagaeal Myotomy. This study reports the efficacy of pneumatic balloon dilatation as a non-surgical motility in achieving relief of dysphagia, clinical improvement and recurrence. Long-term complications were reported.Methods:Eight hundred ninety two adult achalasia patients of both genders were treated from January 1988 till December 2011, with pneumatic balloon (Rigiflex Microvasive®) dilatatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Furthermore, the literature does not help determine the most appropriate timeline to resume oral intake. In the majority of publications, liquid diet was allowed 2 -8 hours after dilation [98,101,103]. We recommend that, in asymptomatic patients in whom there is no suspicion of a full-thickness tear, a soft/normal diet can be initiated on the same day or the day after the procedure.…”
Section: Postoperative Carementioning
confidence: 99%
“…Furthermore, the literature does not help determine the most appropriate timeline to resume oral intake. In the majority of publications, liquid diet was allowed 2 -8 hours after dilation [98,101,103]. We recommend that, in asymptomatic patients in whom there is no suspicion of a full-thickness tear, a soft/normal diet can be initiated on the same day or the day after the procedure.…”
Section: Postoperative Carementioning
confidence: 99%
“…It has been previously shown that the initial results of forced dilatation of the cardia are effective and similar in chagasic or nonchagasic achalasia . The success rates, providing control of dysphagia for at least about 1 year from the procedure using the Rigiflex balloon, are quite satisfactory, with success in at least 75% of patients (Table ) …”
Section: Results Of Pneumatic Dilation In Achalasiamentioning
confidence: 98%
“…32 The success rates, providing control of dysphagia for at least about 1 year from the procedure using the Rigiflex balloon, are quite satisfactory, with success in at least 75% of patients (Table 2). 11,[33][34][35][36][37][38][39][40][41] This was already expressed in a review of 21 studies, where success rates reached 74%, 80%, and 90% using balloons of 30, 35, and 40 mm in diameter, respectively. 42 However, this positive view of using a larger caliber balloon for better results is diminished when it is observed in another publication that, starting with 35 mm balloons, four perforations occurred in the first 13 patients with achalasia submitted to PD, meaning that the protocol had to be adjusted so that the procedure always started with a 30-mm balloon, slowly increasing the gauge if necessary.…”
Section: Results Of Pneumatic Dilation In Achalasiamentioning
confidence: 99%
“…The anal sphincter is evaluated factoring into the proximal plane, the middle plane and the distal plane. [12][13][14] To use kernel regression algorithm to process the ultrasound image effectively removes the blurred image and improves the diagnosis accuracy. Compared with the traditional image, the three-dimensional image in this research was clearer.…”
Section: Discussionmentioning
confidence: 99%